Cobalt- and rhodium-catalyzed carboxylation using carbon dioxide as the C1 source - Fujihara, Tetsuaki; Tsuji, Yasushi (Beilstein Journal of Organic Chemistry, 2018)
Carbon dioxide (CO2) is one of the most important materials as renewable chemical feedstock. In this review, the Co- and Rh-catalyzed transformation of CO2 via carbon–carbon bond-forming reactions is summarized. Combinations of metals (cobalt or rhodium), substrates, and reducing agents realize efficient carboxylation reactions using CO2. The carboxylation of propargyl acetates and alkenyl triflates using cobalt complexes as well as the cobalt-catalyzed reductive carboxylation of α,β-unsaturated nitriles and carboxyamides in the presence of Et2Zn proceed. A Co complex has been demonstrated to act as an efficient catalyst in the carboxylation of allylic C(sp3)–H bonds. Employing zinc as the reductant, carboxyzincation and the four-component coupling reaction between alkyne, acrylates, CO2, and zinc occur efficiently. Rh complexes also catalyze the carboxylation of arylboronic esters, C(sp2)–H carboxylation of aromatic compounds, and hydrocarboxylation of styrene derivatives. The Rh-catalyzed [2 + 2 + 2] cycloaddition of diynes and CO2 proceeds to afford pyrones.
Keywords: carbon dioxide; carboxylation; cobalt; homogeneous catalysts; rhodium